Evaluation method for muscles, measuring mechanomyogram induced by electrical muscle stimulation using lead zirconate titanate-based acoustic sensor. (16th September 2019) - Takei, Yusuke; Takeshita, Toshihiro; Yoshida, Manabu; Kobayashi, Takeshi
Abstract: In this study, we proposed a highly repeatable, quantitative muscle evaluation method whose results are not influenced by the will of the person being measured. We focused on electrical muscle stimulation (EMS) as a method of repetitive muscle contraction, and mechanomyogram (MMG) was measured instead of electromyogram (EMG) to monitor the state of muscle contraction induced by EMS. In order to verify the repeat accuracy of the method, we examined the dispersion of MMG waveform. As a result, it was found that, with regard to the muscle contraction rate and the muscle contraction amount with respect to the electrical stimulation, measurement can be performed with a sufficiently small standard deviation in repeated measurement. It was also confirmed that muscle fatigue caused by continuous electrical stimulation can be measured as a decrease in muscle sound amplitude. By this measurement method, it is possible to quantitatively measure muscle contraction characteristics, muscle fatigue by comparing MMG measured under the same EMS conditions.